Produk Perbankan Syariah: Analisis Akad Penghimpunan Dana, Pembiayaan, dan Penyelesaian Sengketa Murabahah dalam Praktik Perbankan di Indonesia - Fahmi Nuraziz Awaludin; Rayhan Ade Dwiyana; Naufal H (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study examines Islamic banking products with a particular emphasis on the legal analysis of fund-raising contracts, murabahah financing, and dispute resolution mechanisms in Indonesian banking practice. A normative juridical approach is employed to assess the coherence between Sharia principles, positive law provisions, and the contractual implementation adopted by Islamic banks. The findings indicate that fund-raising contracts based on wadiah and mudharabah carry significant legal implications for customer protection and the certainty of contractual relationships. Murabahah financing, as the dominant product, continues to face juridical challenges, notably in relation to the fulfillment of sale-and-purchase elements, margin transparency, and the allocation of risk between banks and customers. Murabahah disputes are commonly triggered by default and imbalanced contractual clauses, necessitating dispute resolution mechanisms that are fair, effective, and consistent with Sharia principles. Resolution through non-litigation processes, Sharia arbitration, and litigation underscores the pivotal role of contract quality as the foundation of legal protection. This study affirms that strengthening the legal aspects of contracts and harmonizing regulations are essential prerequisites for the sustainability of Islamic banking. The findings are expected to contribute conceptually to the development of Islamic banking law and to the sustained enhancement of public trust within a framework of legal justice at the national level.